2014
DOI: 10.3892/ijo.2014.2486
|View full text |Cite
|
Sign up to set email alerts
|

Secretory phospholipase A2-IIa upregulates HER/HER2-elicited signaling in lung cancer cells

Abstract: Lung cancer is the leading cause of cancer death worldwide. There is an urgent need for early diagnostic tools and novel therapies in order to increase lung cancer survival. Secretory phospholipase A2 group IIa (sPLA2-IIa) is involved in inflammation, tumorigenesis and metastasis. We were the first to uncover that cancer cells secrete sPLA2-IIa. sPLA2-IIa is overexpressed in almost all specimens of human lung cancers examined and is significantly elevated in the plasma of lung cancer patients. High levels of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
22
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 51 publications
(60 reference statements)
2
22
0
Order By: Relevance
“…The most recent report by others supports our finding in that high levels of plasma sPLA2-IIa are associated with poor prognosis of cancers (31). More importantly, we revealed that elevated HER/ERBB-PI3K-Akt-NF-κB signaling induces sPLA2-IIa overexpression and secretion in both lung and prostate cancer cells; in turn, sPLA2-IIa stimulates its overexpression via HER/ERBB-elicited signaling in the positive feedback regulation manner (26,32). sPLA2-IIa induces phosphorylation of HER2 and HER3 in a dose-dependent manner in NSCSC A549 and H1975 cells (32).…”
Section: Introductionsupporting
confidence: 89%
See 2 more Smart Citations
“…The most recent report by others supports our finding in that high levels of plasma sPLA2-IIa are associated with poor prognosis of cancers (31). More importantly, we revealed that elevated HER/ERBB-PI3K-Akt-NF-κB signaling induces sPLA2-IIa overexpression and secretion in both lung and prostate cancer cells; in turn, sPLA2-IIa stimulates its overexpression via HER/ERBB-elicited signaling in the positive feedback regulation manner (26,32). sPLA2-IIa induces phosphorylation of HER2 and HER3 in a dose-dependent manner in NSCSC A549 and H1975 cells (32).…”
Section: Introductionsupporting
confidence: 89%
“…Furthermore, sPLA2-IIa directly interacts with and activates EGFR family receptors, suggesting that sPLA2-IIa is a ligand for both EGFR and HER3. These findings, together with our previous data (13,29,30,32), support the notion that high levels of sPLA2-IIa in the tumor microenvironment support CSC phenotype via HER/ERBB-elicited signaling, and sPLA2-IIa is a novel therapeutic target against cancer and CSCs.…”
Section: Introductionsupporting
confidence: 84%
See 1 more Smart Citation
“…1 Histologically, lung cancer is grouped into Non-small (NSCLC) and small-cell lung cancer (SCLC). Platinum-based therapy is commonly used for NSCLC in combination with a tubulin-binding agent, a camptothecin analog, gemcitabine, or pemetrexed.…”
Section: Introductionmentioning
confidence: 99%
“…However transmembrane proteins also can be involved, and they may not have been detected in our pull-down because they are more difficult to isolate and identify by mass spectrometry. In this regard it is worth remembering that both NCL and PLA2g2a interact with integrins and EGFR (47)(48)(49)(50). Since NCL is not a membrane protein, it will have to interact with transmembrane proteins to communicate with the cell interior and trigger the internalization process.…”
Section: Discussionmentioning
confidence: 99%